Efecto de la actividad física en la calidad de vida de una población adulto mayor de Santiago - Cerda A., Lorena; Mascayano M., Marcela; Sanhueza V., Sergio; Abusleme R., Eugenia; Wolf L., Claudia (Revista Hospital Clínico Universidad de Chile, 2011)
ntroduction: Aging involves the loss of functional reserve with alteration of multiple systems. This influences the deterioration of various aspects of health and quality of life. To improve these aspects there are different types of interventions in which physical activity has a prominent role. Objective: To evaluate the effectiveness of one type of physical activity in improving the quality of life of an elderly population of the community. Subjects and methods: We recruited 71 subjects aged 60 years attending a club of elderly. Were randomized into 2 groups (intervention and control) by a blinded observer. The intervention was aerobic physical activity for 30 minutes and calisthenics exercises for heating and cooling, for 10 weeks and 3 times a week. We evaluated 8 dimensions of quality of life at the beginning and end of the intervention by the SF-36. Results: Both groups had similar values at baseline. The intervention group improved clinically (5 to 25 points) and statistically significant (p <0.05) in the 8 dimensions of quality of life. The control group showed a modest improvement in 3 items exploring psychosocial aspects of quality of life. Conclusion: The physical activity in the community is a therapeutic alternative economic, easy to implement, safe to apply and produces a great impact on improving the quality of life of the population over 60 years